Ormond’s Disease – IgG4-related Disease - Miroslav Průcha; Ivan Kolombo; Petr Štádler (Prague Medical Report, 2015)
Ormond’s disease is a relatively rare disease with unclear etiology, characterized by chronic periaortitis and retroperitoneal fibrosis. The inflammatory process affects the infrarenal part of the abdominal aorta and the iliac arteries, and the presence of infiltrates encasing the ureters and inferior vena cava. This disease is currently classed as an IgG4-related disease. In our review we analyse the clinical history, diagnostic approaches, surgical and immunosuppressive therapies.